PENGARUH PENERAPAN PMR TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI DAN RESPON SISWA SMP PADANGSIDIMPUAN - yuni rhamayanti; robi nastain; mhd fahmi lubis (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2021)
SMP as the subject of this research is based on the consideration that the cognitive level is still in the transitional stage from concrete to formal operations so that it is suitable for the implementation of PMR. This study aims to 1) determine the effect of implementing PMR learning on improving students' mathematical communication skills, and 2) knowing student responses during the process of implementing PMR learning. This research is a quasi-experimental research. The design used in this study was a pretest posttest control group design. In this design, there are two groups selected randomly, then given a pretest to determine the extent to which students are ready to receive learning, while the posttest is used to measure students' mathematical communication skills after being given treatment. The research instrument used tests and non-tests. The test used is a test of students' mathematical communication skills in the form of description questions, while the non-test used is a student response questionnaire. Before the test was used, the Expert test and Instrument Trial were conducted at SMP Negeri 3 Padangsidimpuan. The results showed that there was an effect of the application of PMR on the improvement of students' mathematical communication skills. The increase in the mathematical communication ability of the experimental class was 0.63 in the medium category and the control class was 0.24 in the low category. The results of the calculation of student responses to PMR components and activities are 95.55%, this shows a positive student response because the average percentage is > 80%. Based on the results of this study, it is hoped that the application of PMR can be used as an alternative for mathematics teachers to be developed as an effective learning strategy so that mathematics communication skills and student responses are better.